EFFECT OF ASCORBIC ACID ON DNA SYNTHESIS, INTRACELLULAR ACCUMULATION OF ADM AND ADM RESISTANCE OF TUMOR CELL LINES - Xie, Zuofu; Lin, Xiandong; Zhou, Dongmei; Lin, Sheng (Chinese Journal of Cancer Research, 2013)
Objective: To determine the effect of ascorbic acid (AA) on DNA synthesis, intracellular accumulation of ADM and ADM resistance of tumor cell lines. Methods: K562, K562/ADM and KB cell lines were used to study the effect of ascorbic acid on DNA synthesis, intracellular accumulation of ADM and ADM resistance by fluid scintillometry, MTT method, spectrofluorophotometry and immunocytochemistry. Results: Results showed that AA was capable of inhibiting DNA synthesis of K562 and K562/ADM in a dose-dependence fashion, but not KB cell line, and significantly reducing ADM sensitivity in K562 and KB cell lines, as well as potentiating obviously ADM resistance in K562/ADM cell line. Conclusion: These effects of AA may be closely correlated with significant elevation of intracellular accumulation of ADM in KB cell line, and significant reduction of that in K562 and K562/ADM cell lines but possibly not correlated with the expression of Pglycoprotein.